Demokratisasi dan Media Massa di Indonesia - Melati; Muhammad Nurdin; Viola Augustia Putri (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This research analyzes the role of mass media in the democratization process in Indonesia after the fall of the New Order in 1998. Using a literature study method, this research evaluates the role of mass media in disseminating information, facilitating public dialogue, and strengthening government accountability. Political reforms have allowed the media to report important issues more freely, contributing to government transparency and accountability. The mass media also serves as a platform for public discussion, helping the public understand national issues and become more critical voters. However, the mass media faces significant challenges, including intense competition among media channels, dependence on political and economic interests, and the risk of information manipulation. The research results show that despite these challenges, the mass media remains a vital element in promoting democratization in Indonesia by increasing public participation and political transparency. Steps to strengthen media integrity and professionalism, as well as media education for the public, are essential to ensure that the mass media can continue to play a role as a pillar of a healthy and sustainable democracy.